PENGARUH KOMPETENSI KARYAWAN TERHADAP KUALITAS PELAYANAN DEPARTEMEN FRONT OFFICE DI HOTEL PURI SARON SEMINYAK - Kadek Wira Adi Saputra; Pande Putu Juniarta (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
Service Quality is the main basis for knowing the level of customer satisfaction. In this case the company can be said to be good if it is able to provide goods or services in accordance with the wishes of customers. To achieve the goals or objectives that have been determined, a company or organization requires capital, facilities and infrastructure, technology, and Human Resources (HR). Competence is defined as the work ability of each individual which includes aspects of knowledge, skills, and work attitudes that are in accordance with the expected standards. With the majority of employees having competence in accordance with their respective fields of work, it is hoped that they will be able to improve the quality of service to customers or guests who enjoy services at the hotel. The purpose of this study was to determine the effect of employee competence on the quality of service in the front office department at the Puri Saron Seminyak hotel. This research was conducted at Hotel Puri Saron Seminyak. The sample trick method used in this study is the saturated sample method where the samples in this study are all front office employees at the Puri Saron Seminyak hotel. Based on the results of the research that has been done, it shows that the employee competency variable (X) shows a positive and significant influence on the service quality variable (Y) at the Puri Saron Seminyak Hotel and the employee competency variable contributes 31.6% to the service quality of front office employees at Hotel Puri Saron Seminyak.